Reflexões sobre a colonização e a colonialidade no início do século XXI - Neto, Vitale Joanoni (Diálogos Latinoamericanos, 2015)
This article proposes to deal with multiculturalism in the contemporary world and does so relational. From the sixteenth century the Western world was divided between metropolises and colonies, with clear roles assigned to each of these parts: it was the first occupation and exploitation of natural and human resources of the territories under his command and to the second reduce their existence to condition dependent, producing what is allowed him as and when it was determined. International capital took its first steps toward the construction of its hegemony, this first time in close partnership with the nascent nations-states. The crisis of paradigms and the internationalization of capital imposed other ideologies, other discourses, including respect for identities, the coexistence of hybrid worlds culturally different to what he called multiculturalism.